2,6-Bis(benzo[b]thiophen-2-yl)-3,7-dipentadecyltetrathienoacene (DBT-TTAR2) as an Alternative of Highly Soluble p-Type Organic Semiconductor for Organic Thin Film Transistor (OTFT) Application - Mery B. Supriadi; Ming-Chou Chen; You-Shan Li (Chemistry Department, The University of Brawijaya, 2013)
A new compound of organic semiconductor based on tetrathienoacene (TTA) derivatives, DBT-TTAR2 was synthesized and characterized. The corporation of dibenzo[b,d]thiophene (DBT) group and alkyl substituent in both ends of TTA core have a significant effect on their π-π molecular conjugation length, energy gaps value and solubility properties. DBT-TTAR2 is fabricated as p-type organic semiconductor of organic thin film transistor (OTFT) by solution process at Industrial Technology Research Institute, Taiwan. A good optical, electrochemical, and thermal properties of DBT-TTAR2 showed that its exhibits a better performance as highly soluble p-type organic semiconductor.